2023
DOI: 10.3390/jmse11051083
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Impact on Summer Precipitation and Moisture Fluxes over the Mexican Altiplano

Abstract: In the warm season, El Niño/Southern Oscillation (ENSO) causes periods with more rain in Northern Mexico during its positive phase, while less rainfall is recorded in the southern regions during the negative phase. This research study evaluates the variability of summer (July–September) precipitation and moisture fluxes under different ENSO scenarios in the Mexican Altiplano and coast of the state of Nayarit. The catchment of Rio San Pedro-Mezquital (SPM-RB) connects both regions. Using the Oceanic Niño Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On the contrary, in Baja California precipitation could increase during the GS, consistent with other model results (Cavazos & Arriaga-Ramírez, 2012), while there could be a minimal decrease in winter, but with high variation due to atmospheric rivers (Gershunov et al, 2019), extreme events (Avila-Diaz et al, 2022), and changes in natural oscillations, such as El Niño-Southern Oscillation (IPCC, 2021). The Mexican HP region is also affected by ENSO variations during the summer and winter (e.g., Vega-Camarena et al, 2023). Jones and Goodrich (2008) state that climatic variability could be of equal importance to the wine industry as climate change.…”
Section: Future Changesmentioning
confidence: 99%
“…On the contrary, in Baja California precipitation could increase during the GS, consistent with other model results (Cavazos & Arriaga-Ramírez, 2012), while there could be a minimal decrease in winter, but with high variation due to atmospheric rivers (Gershunov et al, 2019), extreme events (Avila-Diaz et al, 2022), and changes in natural oscillations, such as El Niño-Southern Oscillation (IPCC, 2021). The Mexican HP region is also affected by ENSO variations during the summer and winter (e.g., Vega-Camarena et al, 2023). Jones and Goodrich (2008) state that climatic variability could be of equal importance to the wine industry as climate change.…”
Section: Future Changesmentioning
confidence: 99%
“…For instance, unlike our results, Pavia, Graef, and Reyes [14] found that for mean temperature, cooler conditions are favored during La Niña summers and El Niño winters regardless of the PDO phase, and a high PDO favors warmer conditions during El Niño summers. This situation is complicated when moisture (i.e., rainfall) and ENSOs are correlated [64,65]. However, the connection between below-average winter precipitation and La Niña events is much stronger than that between above-average winter precipitation and El Niño events [66].…”
Section: Interannual Variationmentioning
confidence: 99%
“…Many studies have attempted to establish a relationship between ENSO phases and rainfall in northwestern Mexico. For instance, Vega-Camarena, Brito-Castillo, Pineda-Martínez, and Farfán [64] andVega-Camarena, Brito-Castillo, Farfán, Gochis, Pineda-Martínez, and Díaz [65] found that rainfall production in the Altiplano (Mexican Plateau), located to the south of the monsoon region, depends not only on the ENSO phase but also on the phase combination between PDO and AMO. They concluded that above-average rainfall occurs from the transition from El Niño to La Niña or La Niña to El Niño events.…”
Section: Interannual Variationmentioning
confidence: 99%
“…Droughts or precipitation deficit over the CAM domain have been partially attributed to individual or combined phases of different teleconnections, such as El Niño-Southern Oscillation (ENSO), the Pacific Multidecadal Oscillation (PDO) and the Atlantic Multidecadal Oscillation (AMO) (e.g., Abiy et al, 2019;Aryal & Zhu, 2021;Cavazos et al, 2020;Gershunov & Barnett, 1998;Hidalgo et al, 2015;McCabe et al, 2004;McCrary & Randall, 2010;Méndez & Magaña, 2010;Seager et al, 2009;Vega-Camarena et al, 2018Zermeño-Díaz & Mendoza, 2023). For example, drier years over the southwest United States and northwest Mexico, and wetter years in the MSD, have been linked to negative ENSO (La Niña) phases (Cook et al, 2007;Hoerling & Kumar, 2003;Méndez & Magaña, 2010;Seager et al, 2009;Vega-Camarena et al, 2023;Zermeño-Díaz & Mendoza, 2023), and the positive AMO (Abiy et al, 2019;Aryal & Zhu, 2021;Cavazos et al, 2020;Méndez & Magaña, 2010). Méndez and Magaña (2010) also observed that during the negative PDO, there is a weakening of the Caribbean low-level jet and an increase in easterly waves that could be related to droughts (wet period) in northern Mexico (MSD) due to increased tropical convection, which induces less northward moisture influx and subsidence west of the convection region.…”
Section: Introductionmentioning
confidence: 99%